Sturge-Weber syndrome with gingival hyperplasia: A case report - Otakhoigbogie, Uwaila U.; Osagbemiro, Babatope B.; Nathaniel, Godswill I.; Eke, Gracia K.; Akadiri, Oladimeji A.; Dirisu, Nana O. (Hasanuddin University, 2020)
Introduction: Sturge-Weber syndrome (SWS) is a relatively rare condition amongst the port-wine birthmark, and it is the most common with the incidence of 0.3% in live births. It is a neurocutaneous syndrome, characterised by a facial port-wine stain, leptomeningeal angioma and glaucoma.Â Case report: This is a case report of a 20-year-old mentally disabled boy with port-wine nevi on the right side of the face along the distribution of trigeminal nerve extending over the neck and shoulder, early childhood seizures, intracranial calcification, glaucoma and gingival enlargement with bleeding on slight probing that was managed conservatively.Conclusion: Management of a patient with Sturge-Weber syndrome is usually multidisciplinary. Gingival enlargement can impair the maintenance of oral hygiene, leading to the accumulation of plaque and calculus. Gingivectomy of angiomatous gingival enlargement should be performed with caution because the tissues may bleed profusely intraoperatively and postoperatively.